PERKEMBANGAN ASAS REBUS SIC STANTIBUS (PERUBAHAN KEADAAN YANG FUNDAMENTAL) DALAM HUKUM POSITIF DI INDONESIA - Suherman Suherman (Jurnal Yuridis, 2017)
Rebus Sic Stantibus Principle is a change of circumstances be applied if theprovisions and terms of the contract change was not due to the impossibility of theexecution of the contract, but due to the extreme difficulty for either party to fulfill the contract. The entity of rebus sic stantibus principle in positive law in Indonesia,stipulated in article 18 of Law No. 24 of 2000 on international agreements represent that "international agreements terminate if there are substantial changes that affect the implementation of the agreement". While in the Civil Code we do not recognize this principle. In the field of civil law known several reasons that can be used to terminate the agreement, as stipulated in Article 1381 of the Civil Code.